Discourse Markers Analysis In The Ron Clark Story Movie - Ridhoni Akbar; Nanik Mariani; Eka Puteri Elyani (Institut Agama Islam Negeri Palopo, 2023)
This research investigates the discourse makers found in The Ron Clark Story movie. Discourse makers are words that link the speaker to what has been uttered previously. This can improve a speaker's ability to communicate clearly. This research analyzes the discourse makers found in every scene The Ron Clark Story movie. A qualitive descriptive method was used to analyze the collected data. The result of this study the discourse marker